Intertemporal Choice: Decision Making and Time in Software Engineering - Becker, Christoph; Walker, Dawn; McCord, Curtis (2017 IEEE/ACM 10th International Workshop on Cooperative and Human Aspects of Software Engineering (CHASE), 2017)
When making choices in software projects, engineers and other stakeholders engage in decision making that involves uncertain future outcomes. The concept of 'intertemporal choice' describes choices between outcomes at different times in the future. Short-sighted decisions with far-reaching effects are a long-standing cause of concern in the software profession. Common models to support decisions in software projects use concepts such as expected utility and discount factors to quantify future value and enable trade-off decisions. However, a growing body of behavioral research shows that these normative models do not adequately describe how people actually make choices. Our objective is to understand how developers and stakeholders actually take trade-off decisions during software projects that involve current and future benefits, and to identify the human and cooperative factors that influence them. This requires empirical research on decision making in SE with a focus on trade-offs across time. To support such research, this paper reports on a systematic literature review that aimed to identify whether the intersection of these concepts has been acknowledged and addressed. We discuss the assumptions about decision makers that underpin existing research and analyze how the role of time has been characterized in the study of decision making in SE. Based on this review, the paper begins to develop principles for a descriptive framework to characterize intertemporal choices in empirical and behavioral software engineering research.